Activity-Dependent Netrin-1 Secretion Drives Synaptic Insertion of GluA1-Containing AMPA Receptors in the Hippocampus - Stephen D. Glasgow; Simon Labrecque; Ian V. Beamish; Sarah Aufmkolk; Julien Gibon; Dong Cho Han; Stephanie N. Harris; Paul Dufresne; Paul W. Wiseman; R. Anne McKinney; Philippe Séguéla; Paul De Koninck; et al. (2018)
Dynamic trafficking of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptors (AMPARs) to synapses is critical for activity-dependent synaptic plasticity underlying learning and memory, but the identity of key molecular effectors remains elusive. Here, we demonstrate that membrane depolarization and N-methyl-D-aspartate receptor (NMDAR) activation triggers secretion of the chemotropic guidance cue netrin-1 from dendrites. Using selective genetic deletion, we show that netrin-1 expression by excitatory neurons is required for NMDAR-dependent long-term potentiation (LTP) in the adult hippocampus. Furthermore, we demonstrate that application of exogenous netrin-1 is sufficient to trigger the potentiation of excitatory glutamatergic transmission at hippocampal Schaffer collateral synapses via Ca2+-dependent recruitment of GluA1-containing AMPARs, promoting the maturation of immature or nascent synapses. These findings identify a central role for activity-dependent release of netrin-1 as a critical effector of synaptic plasticity in the adult hippocampus.